Cerebral Venous Thrombosis in Behçet's Disease Patients Compared to Other Causes of Cerebral Venous Thrombosis: a Retrospective Study - Mine Hayriye SORGUN,; Sefer RZAYEV,; Mustafa Aykut KURAL,; Seyda ERDOĞAN,; Canan YÜCESAN, (Archives of Rheumatology, 2016)
Objectives: This study aims to report the outcomes of patients with Behçet’s disease (BD) with cerebral venous thrombosis (CVT) due to BD compared to patients with CVT due to other causes and to discuss the treatment options. Patients and methods: Files of 47 patients admitted to our outpatient clinic for CVT between January 2007 and November 2014 were retrospectively reviewed. Patients were divided into two groups; group 1 included 21 CVT patients with BD (9 males, 12 females; mean age 47±12 years; range 27 to 69 years) and group 2 included 26 CVT patients without BD (11 males, 15 females; mean age 45±16 years; range 25 to 79 years). We collected data for diagnosis for BD and CVT, duration of all medications, functional system involvement, baseline Expanded Disability Status Scale scores, modified Rankin Scale scores at follow-up, and localizations of lesions in brain magnetic resonance imaging and magnetic resonance venography. Results: Mean follow-up duration was four years in group 1 and two years in group 2. There was no significant difference between the groups regarding age, sex, neurological symptoms/findings and baseline Expanded Disability Status Scale scores. Localizations of occluded sinus in group 1 and group 2 were similar. For acute CVT, patients were treated with intravenous high dose prednisolone in group 1 and with anticoagulant in group 2. Follow-up modified Rankin Scale score was 0 in both groups. Conclusion: Our study revealed similar clinical and radiological findings in CVT patients with or without BD. Although medications used for treatment were different between the groups, treatment responses were good in both groups. Treatment with prednisolone may be sufficient and anticoagulation therapy may not be necessary for acute CVT attacks in BD.